2020
DOI: 10.1007/s00467-020-04769-z
|View full text |Cite
|
Sign up to set email alerts
|

Tandem plasmapheresis and continuous kidney replacement treatment in pediatric patients

Abstract: Background The objectives of the study are to describe tandem therapeutic plasma exchange (TPE) and continuous kidney replacement therapy (CKRT) patients' outcomes in a large institution. Methods We reviewed pediatric patients receiving tandem TPE and CKRT from 2013 to 2016. Over the study period, 63 discrete patients received tandem TPE and CKRT for a total of 378 TPE procedures on 1676 days on CKRT. Results Patient age ranged from newborn to 19 years old with weights ranging from 2.31 to 112.3 kg (17 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…There is scant literature on the use of TPE in children. Recently, Pekkucuksen et al [13] reported on their experience with TPE also at a large institution in 63 pediatric patients with a similar range of clinical diagnoses when compared to our study. In contrast to our study, they did not investigate the impact of tandem TPE on circuit downtime, but importantly the authors report on the safety of concurrent CRRT with TPE.…”
Section: Discussion/conclusionsupporting
confidence: 76%
See 3 more Smart Citations
“…There is scant literature on the use of TPE in children. Recently, Pekkucuksen et al [13] reported on their experience with TPE also at a large institution in 63 pediatric patients with a similar range of clinical diagnoses when compared to our study. In contrast to our study, they did not investigate the impact of tandem TPE on circuit downtime, but importantly the authors report on the safety of concurrent CRRT with TPE.…”
Section: Discussion/conclusionsupporting
confidence: 76%
“…Our study has a number of positive features that lend credence to our findings. Our patient population undergoing concurrent CRRT and TPE both before and after initiation of the tandem TPE protocol is comparable to or larger than similar reports [7, 13, 16]. Our broad inclusion criteria, with all patients undergoing CRRT during the study period included in the analysis, are also a strength with respect to the generalizability of our findings.…”
Section: Discussion/conclusionsupporting
confidence: 55%
See 2 more Smart Citations
“…This was alternated with combined plasma exchange and haemodialysis (for n = 8). Plasma exchange was 1.5 × plasma volume 5/10 (50%) died 3/10 (30%) others were successfully transplanted 2/10 (20%) had native liver survival Patients showed significantly greater reductions in bilirubin, ammonia and INR on PE/HD than on MARS/mini-MARS ( p < 0.05) Tufan Pekkucuksen et al 2020 [ 48 ] 2013–2016 USA Retrospective observational cohort study n = 63 ( n = 20, 32% TPE for ALF or ACLF) Tandem continuous veno-venous haemodiafiltration and plasma exchange. For plasma exchange; mean exchange volume 1.34 + / − 0.21.…”
Section: Evidence For Plasma Exchange In Paediatricsmentioning
confidence: 99%